A study on ridership capacity analysis at rapid Kelana Jaya Line Station - Mohd Arif, Muhammad Farhan (2017)
Level of Service (LOS) is commonly used to access the quality of operations of transportation facilities at the roadside. However, LOS, measures for pedestrian facilities such as waiting areas are not well developed until now. The main objective of this study is to determine the level of service of platform at KELANA JAY A LINE KL SENTRAL station, in order to identify the current operational conditions. Objectives are achieved by referring to LOS standards from Highway Capacity Manual (2000) and Transit Capacity and Quality of Service Manual (TCQSM). Additionally, analysis has been canied out for peak hours and focus on KL Sentral Station platform. Results showed that, LOS at platform was LOS E and there are a few LOS D and LOS A during the peak hours. The probability of worse LOS levels in the future are high. Based on analysis data, access way front and the end of platform edge were identified as areas that are highly crowded. Results from this study could be used as a guide by authorities and management team of the station to detect and monitor the LOS of the platforn1. Hence, could provide better service that matches the right level of service and provides higher passenger comfort, while using the service. The capacity of a transit mode refers to bow many passengers per hour a mode can be expected to cany. Since when we discuss capacity we are usually discussing it in tenns of a rapid transit project, the capacity should be defined as the maximum number of passengers per hour a given mode could carry at its maximum average operating speed. Overall, the capacity of a given transit mode expressed in passengers per hour can be represented as the result of multiplying the nwnber of vehicle trains that could pass by a particular stop in one hour which is frequency by the number of vehicles per train and the number of passengers that could be canied by each vehicle.